Implementation of hybrid SSA–SA based three-degree-of-freedom fractional-order PID controller for AGC of a two-area power system integrated with small hydro plants - Nayak, Jyoti Ranjan; Shaw, Binod; Sahu, Binod Kumar (IET generation, transmission & distribution, 2020)
In this work, a comparative study is analysed between the fractional-order controllers such as fractional-order proportional–integral–derivative (FOPID), two-degree-of-freedom proportional–integral–derivative (DOF FOPID) and 3DOF FOPID, and conventional controllers such as proportional–integral–derivative (PID), 2DOF PID and 3DOF PID employed in automatic generation control (AGC) in power system. The proposed 3DOF FOPID controller is validated as superior one among all other controllers. The gains of all the controllers are optimally plucked by novel salp swarm algorithm (SSA). Further, hybrid salp swarm algorithm–simulated annealing (hSSA-SA) algorithm is introduced to enhance the proficiency of 3DOF FOPID controller by sensibly plucking the gain parameters. The proposed approaches are implemented in a two-area thermal-hydro-diesel system. Small hydro plants (SHPs) of similar characteristics are enforced in both areas with their dynamic responses by conceding frequency deviations of each area. Further, sensitivity and robustness analysis of the system with and without SHP are observed by varying some important parameters of the system. Finally, the supremacy of three novel approaches (fractional based controllers, hSSA-SA and SHP) is substantiated gracefully.